(untitled) (Bangladesh Journal of Medical Science, 2026)
Aim The aim of this study was to analyze the early results of creating a colostomy in children with anorectal malformations (ARM) by forming an aponeurotic ring. The frequency of postoperative complications after using a modified technique and a traditional approach was compared. Methods A retrospective study was carried out in Scientific Center of Pediatrics and Pediatric Surgery, Almaty, Kazakhstan from 2014 to 2023. The 63 patients under the age of 4 with ARM were included in the study and divided into two groups. The former group comprised patients who had stoma creation performed via the conventional technique. The second group consisted of patients who had stoma established by forming an aponeurotic ring. Results The predominant types of surgical intervention in both groups were end and divided colostomies. In the first group of 35 children, 10 had postoperative complications (28.5%). Early complications developed in 4 children, late complications in 6 children. In the second group of 28 children, complications developed in 2 patients (7.2%): in one case on the 6th day of life, and in another case after 2 months. Out of 63 children, one child died during treatment. Conclusions Compared to the conventional method, an aponeurotic ring-assisted stoma formation method allowed to reduce the risk of early and late stoma-associated complications by 4 times (RR=0.25, p=0.051). BJMS, Vol. 25 No. 01 January’26 Page : 353-359